Nasal palatal: segment complex - Romera, Lourdes; Fernández, Ana M. (Caplletra. Revista Internacional de Filologia, 1995)
This paper focuses on the nature of a segment which is always problematical —the palatal nasal. Phonetic results found in the acoustic, perceptive and articulate spheres, showing the different features of this nasal with regards to others, are the point of departure for a brief reflection on the phonological nature of this segment, taking into account the feature geometry and the articulatory phonology. It concludes by considering the palatal nasal /?/ as a complex segment formed by /n+j/ and the imputation, to temporary effects, of a degree of major o minor assimilation and gestural overlapping during effective perception of /?/, of /n+j/ or of /n+i/.